Wildwood imperium - Meloy, Colin (Meloy, Colin. Wildwood chronicles, 2014)
In the aftermath of a young's girl's midnight seance that awakens a long-slumbering, malevolent spirit, a band of runaway orphans teams up with an underground collective of saboteurs to rescue friends imprisoned in an industrial wasteland.